1990
DOI: 10.1152/ajpendo.1990.258.2.e304
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and gastric myoelectrical responses to illusory self-motion in humans

Abstract: We compared gastric myoelectrical activity and endogenous neuroendocrine responses in subjects with and without motion sickness elicited by illusory self-motion or vection. Rotating a drum with black and white vertical stripes around seated stationary subjects (n = 22) produced vection. Gastric myoelectrical activity was recorded with cutaneous electrodes. Thirteen subjects developed gastric dysrhythmias [4- to 9-cycles/min (cpm) signals] and motion sickness during vection, whereas nine subjects maintained nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 23 publications
5
64
3
Order By: Relevance
“…As expected, these patterns of autonomic response were observed in conjunction with a decrease in 3-cpm gastric myoelectrical activity and an increase in gastric tachyarrhythmia. These findings are consistent with prior motion sickness research showing that similar patterns of gastric myoelectrical reactivity are observed in conjunction with a reciprocal pattern of autonomic response (Hasler et al, 1995;Hu et al, 1991;Koch, Stern, Vasey, Seaton et al, 1990;Money et al, 1996;Uijtdehaage et al, 1992). We do not recommend, however, that inferences regarding gastric autonomic activity be made from PEP or RSA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, these patterns of autonomic response were observed in conjunction with a decrease in 3-cpm gastric myoelectrical activity and an increase in gastric tachyarrhythmia. These findings are consistent with prior motion sickness research showing that similar patterns of gastric myoelectrical reactivity are observed in conjunction with a reciprocal pattern of autonomic response (Hasler et al, 1995;Hu et al, 1991;Koch, Stern, Vasey, Seaton et al, 1990;Money et al, 1996;Uijtdehaage et al, 1992). We do not recommend, however, that inferences regarding gastric autonomic activity be made from PEP or RSA.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, several studies have shown that the expression of gastric tachyarrhythmia during the experience of nausea is associated with an increase in sympathetic and decrease in parasympathetic activation . Prior research, for example, has shown that motion sickness-induced gastric tachyarrhythmia is associated with decreased parasympathetic cardiac activity (Hu, Grant, Stern, & Koch, 1991;Uijtdehaage, Stern, & Koch, 1992, increased skin conductance Miller, Sharkey, Graham, & McCauley, 1993), and increased plasma catecholamine levels (Koch, Stern, Vasey, Seaton et al, 1990). Prior experiments investigating the effects of laboratory stressors on gastric myoelectrical activity have shown that 3-cpm activity decreases in response to the cold pressor test (Riezzo, Porcelli, Guerra, & Giorgio, 1996;Stern, Vasey, Hu, & Koch, 1991) and viewing aversive films (e.g., limb mutilation; Stewart, 1987), and that 3-cpm activity decreases and gastric tachyarrhythmia increases during shock avoidance (Muth, Koch, Stern, & Thayer, 1999).…”
mentioning
confidence: 99%
“…Motion or intravenous infusion of vasopressin elicited gastric dysrhythmia in humans, and the dysrhythmia was recording prior to reported nausea (Stern et al, 1987;Koch et al, 1990a;Caras et al, 1997). Gastric dysrhythmia is closely correlated with reported nausea in a variety of conditions that produce nausea, including surgery, pregnancy and chemotherapy (Pezzolla et al, 1991;Riezzo et al, 1992;DiBaise et al, 2001).…”
Section: Neurohypophyseal Hormonal Secretions and Gastric Dysrhythmiamentioning
confidence: 99%
“…Koch et al [29] have shown that subjects who subsequently develop symptoms of motion sickness when exposed to a rotating optokinetic drum have a significantly higher level of peripheral beta-endorphins than subjects who experienced no symptoms. It was suggested that central endorphins might play a role in inhibiting the development of optokinetic motion sickness.…”
Section: Discussionmentioning
confidence: 99%
“…During drum rotation, neurosensory afferent information from the vestibular and proprioceptive systems indicates no movement of the individual. Thus in susceptible subjects, the rotating drum induces a neurosensory mismatch that results in the symptoms of nausea and tachygastria and increased beta-endorphin [29], vasopressin [30,32], and epinephrine [33]. However, neurohumoral mechanisms that mediate vection-induced tachygastria are still not well understood.…”
Section: (A) (B) (C)mentioning
confidence: 99%